Acute effects of a static vs. a dynamic stretching warm-up on repeated-sprint performance in female handball players - Zmijewski, P.; Lipinska, P.; Czajkowska, A.; Móz, A.; Kapuscinski, P.; Mazurek, K. (Journal of Human Kinetics, 2020)
This randomized cross-over study examined the effects of typical static and dynamic stretching warm-up protocols on repeated-sprint performance. Thirteen young female handball players performed a 5 min aerobic warm-up followed by one of three stretching protocols for the lower limbs: (1) static stretching, (2) dynamic-ballistic stretching, and (3) no stretching before performing five all-out sprints on a cycle ergometer. Each protocol was performed on a different occasion, separated by 2-3 days. Range of movement (ROM) was also measured before and after the warm-up protocols with a sit-and-reach test. Fixed and random effects of each stretching protocol on repeated sprint performance were estimated with mixed linear modeling and data were evaluated via standardization and magnitude-based inferences. In comparison to no stretching, there were small increases in ROM after dynamic stretching (12.7%, ±0.7%; mean, ±90% confidence limits) and static stretching (19.2%, ±0.9%). There were small increases in the average power across all sprints with dynamic stretching relative to static stretching (3.3%, ±2.4%) and no stretching (3.0%, ±2.4%) and trivial to small increases in the average power in the 1st and 5th trials with dynamic stretching compared to static stretching (3.9%, ±2.6%; 2.6%, ±2.6%, respectively) and no stretching (2.0%, ±2.7%; 4.1%, ±2.8%, respectively). There were also trivial and small decreases in power across all sprints with static relative to dynamic stretching (-1.3%, ±2.8%) and no stretching (-3.5%, ±2.9%). Dynamic stretching improved repeated-sprint performance to a greater extent than static stretching and no stretching. Key words: performance, team sport athletes, high-intensity, modeling